Covalent Organic Framework with Highly Accessible Carbonyls and π‐Cation Effect for Advanced Potassium‐Ion Batteries. Issue 10 (31st January 2022) - Luo, Xiao‐Xi; Li, Wen‐Hao; Liang, Hao‐Jie; Zhang, Hong‐Xia; Du, Kai‐Di; Wang, Xiao‐Tong; Liu, Xin‐Fang; Zhang, Jing‐Ping; Wu, Xing‐Long
Abstract: Covalent organic frameworks (COF) possess a robust and porous crystalline structure, making them an appealing candidate for energy storage. Herein, we report an exfoliated polyimide COF composite (P‐COF@SWCNT) prepared by an in situ condensation of anhydride and amine on the single‐walled carbon nanotubes as advanced anode for potassium‐ion batteries (PIBs). Numerous active sites exposed on the exfoliated frameworks and the various open pathways promote the highly efficient ion diffusion in the P‐COF@SWCNT while preventing irreversible dissolution in the electrolyte. During the charging/discharging process, K + is engaged in the carbonyls of imide group and naphthalene rings through the enolization and π‐K + effect, which is demonstrated by the DFT calculation and XPS, ex‐situ FTIR, Raman. As a result, the prepared P‐COF@SWCNT anode enables an incredibly high reversible specific capacity of 438 mA h g −1 at 0.05 A g −1 and extended stability. The structural advantage of P‐COF@SWCNT enables more insights into the design and versatility of COF as an electrode. Abstract : We prepare a polyimide covalent organic framework composite anode by effective in‐situ condensation of anhydride and amine on the surface of single‐walled carbon nanotubes. The construction of the conductive network accelerates the transport of electron. Dual electroactive sites in the framework, carbonyls and aromatic naphthalene rings, could store more potassium ions by the enolization and π‐K + effect.